LITERARY-AESTHETIC VIEWS IN TRANSLATION AND THE PROBLEM OF CREATIVE PARALLELISM (ON THE EXAMPLE OF TRANSLATIONS OF JANE AUSTEN’S WORKS) - Erkinova Aziza (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Literary translation involves transferring meaning while preserving stylistic and aesthetic qualities. This study examines literary-aesthetic perspectives and the problem of creative parallelism through the works of Jane Austen. Findings indicate that creative adaptation is essential for preserving artistic integrity.